Exosomes in Cholesterol Metabolism and Atherosclerosis - Reiss, Allison B.; Vernice, Nicholas A.; Siegart, Nicolle M.; De Leon, Joshua; Kasselman, Lora J. (Cardiovascular & Haematological Disorders - Drug Targets, 2017)
Objective: Exosomes are small secreted membrane vesicles formed in the late endocytic compartments by inward budding. Interest in these extracellular vesicles and their role in atherosclerosis is growing, as they can affect multiple cellular processes that lead to lipid overload, cytokine secretion and cellular adhesion. Exosomes protect and transport lipids, proteins, and RNAs, fostering intercellular communication among different cell types involved in atherogenesis such as macrophages, endothelium and smooth muscle. Their molecular composition reflects their cell type of origin, but they share attributes because they are enriched in proteins of their endosomal source. Conclusion: This review will describe the current state of our knowledge of exosome involvement in the development of atherosclerosis. The transfer of signaling molecules, lipids, mRNAs, and microRNAs via exosomes with effects on monocyte and macrophage cholesterol metabolism, endothelial cell and platelet activation and smooth muscle proliferation will be discussed. Finally, therapeutic potential of exosomes and clinical application will be explored.
Keywords: cholesterol